Reasons for the migration of church members from one congregation to another - I. M. Bredenkamp; W. J. Schoeman (Acta Theologica)
This article aims to determine the reasons why members of one congregation migrate to another, and to identify factors that play a role in this process. These are determined by the nature and functioning of congregations. This qualitative research involved members of three different congregations that had recently experienced a positive growth in membership numbers. The effects of secularisation and the Enlightenment, and their consequences at various levels, as well as the theories of McDonaldisation and Consumerism were taken into consideration to explain the migration of church members between congregations. The answer is not simple in the sense that two tendencies can be identified: ‘push’ factors that activate the tendency to move out of the previous congregation, and a drawing or ‘pulling’ tendency, representing those factors that attract people. It can be stated that the reasons for migration can, to a large extent, be traced to the nature and functioning of the congregation. In addition, clear tendencies can be identified in terms of ‘push’ and ‘pull’ factors.